Vloga anksioznosti pri spolnih motnjah - Kozina, Ana (Psihološka obzorja (Ljubljana), 2006)
Anxienty is closely related to sexual disorders, being their source, preserver, and consequence. Therefore, it represents an important obstacle in the course of a therapy. The role of anxiety in sexual disorders has already been widely investigated, but the question whether the above mentioned connection exists at a micro level remains unanswered. The present study focused on two specific anxiety disorders: agoraphobia and obsessive compulsive disorder. Two translated questionnaries were used: Mobility Inventory for Agoraphobia MIA (Chambless, Caputo, Jasin, & Gracely, 1985) and Padua Inventory PI (Sanavio, 1988). Participants were patients with sexual disorders who sought psychiatric help, and a group of students represented a control group. Results demonstrated a strong connection between agoraphobic and obsessive compulsive symptoms on one side and sexual disorders on the other. Among the possible explanations for this connection the circular model seems to be the most appropriate.
Keywords: anksioznost; agorafobija; obsesivno kompulzivna motnja; spolne motnje; psihologija; psychology